Standardised (plain) packaging: the time for implementation has come - Daube, Michael; Hoek, J.; Edwards, R. (NZMA, 2015)
Although a growing number of countries have passed legislation to introduce standardised (or ‘plain’) packaging, New Zealand’s legislation is currently stalled. The research evidence supporting standardised packaging is strong; furthermore, evaluations from Australia, the first country to introduce this measure, show standardised packaging is reducing the appeal of smoking. Tobacco consumption in Australia has also fallen since the introduction of standardised packaging. The government should reassert its commitment to New Zealand’s smokefree 2025 goal by recognising the Australian evidence and passing and implementing standardised packaging as soon as possible.